\begin{tabular}{l} What is \( (a \cdot p)(x) \) ? \\ \( \qquad p(x)=-2 x^{2} \) \\ \( p(x)=x^{2}+5 x-6 \) \\ Write your answer as a polynomial or a rational function in simplest form. \\ \hline 2 \end{tabular}
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Beyond the Answer
To find \( (a \cdot p)(x) \), we first need to clarify what \( a \) represents. Assuming \( a \) is a scalar, for each case of \( p(x) \), we can perform the multiplication by \( a \) accordingly. 1. For the first polynomial \( p(x) = -2x^2 \): \[ (a \cdot p)(x) = a \cdot (-2x^2) = -2a x^2 \] 2. For the second polynomial \( p(x) = x^2 + 5x - 6 \): \[ (a \cdot p)(x) = a \cdot (x^2 + 5x - 6) = ax^2 + 5ax - 6a \] Thus, your final expressions in simplest form for each polynomial are: - For \( p(x) = -2x^2 \), the result is \( -2a x^2 \). - For \( p(x) = x^2 + 5x - 6 \), the result is \( ax^2 + 5ax - 6a \).